Management of salivary gland adenoid cystic carcinoma: institutional experience of a case series - Tincani, Alfio José; Negro, André Del; Araújo, Priscila Pereira Costa; Akashi, Hugo Kenzo; Martins, Antonio Santos; Altemani, Albina Milani; Barreto, Gilson (São Paulo Medical Journal, 2006)
CONTEXT AND OBJECTIVE: Salivary gland tumor management requires long-term follow-up because of tumor indolence and possible late recurrence and distant metastasis. Adenoid cystic carcinoma (ACC) accounts for 10-15% of such tumors. The aim here was to evaluate surgical and clinical management, staging and follow-up of ACC patients in one academic institution. DESIGN AND SETTING: Retrospective study at Head and Neck Service, Universidade Estadual de Campinas. METHODS: Data on 21 patients treated between 1993 and 2003 were reviewed. Management utilized clinical staging, histology and imaging. Major salivary gland tumor extent was routinely assessed by preoperative ultrasonography. Diag- nosis, surgery type, margin type (negative/posi- tive), postoperative radiotherapy and recurrence (presence/absence) were evaluated. RESULTS: There were eleven major salivary gland tumors (52.3%), seven submandibular and four parotid. Ten patients (47.7%) had minor salivary gland ACC (all in palate), while the submandibular was the most frequently affected major one. Diagnoses were mostly via fine-needle aspiration (FNA) and incision biopsy. Frozen sec- tions were used for six patients. There was good ultrasound/FNA correlation. Sixteen (76%) had postoperative radiotherapy. One (4.7%) died from ACC and five now have recurrent disease: three (14.2%) locoregional and two (9.5%) distant metastases. CONCLUSION: Adenoid cystic carcinoma has locally aggressive behavior. In 21 cases, of ACC, the facial nerve was preserved in all except in the few with gross tumor involvement. Treatment was defined from physical examination, imaging, staging and histology.